Food waste from Parkia biglobosa seed processing as a potential biomass resource for valorization - Oludipe, Emmanuel Olorunleke; Ajayi, Ayodele Oluwaseun; Owolabi, Akinyomade Oladipo; Olojede, Ayoyinka Olufunke; Afolabi, Yemisi Tokunbo; Nwonuma, Charles Obiora; Adewumi, Blessing Grace; Dada, Ebenezer Olasunkanmi; Owa, Stephen Oluwagbemiga (Frontiers in Sustainable Food Systems, 2024)
Research into potential valorization of agricultural waste from indigenous Sub-Saharan African food processes remains largely unexploited. By-products from Parkia biglobosa seed processing into condiment have been associated with negative perceptions as pollutants. This research assessed its potential development for various industrial application. In this study, a standardized protocol was adopted in the processing of P. biglobosa seed into condiment, this enabled the quantification of food and by-products generated in percentage. A comparative analysis of the proximate and mineral constituent of the dried food condiment and seed coat (testa) was conducted. Furthermore, the phytochemical constituent of effluents from the two stages of processing were characterized using qualitative and quantitative methods, including Fourier-transform infrared spectroscopy (FTIR) and Gas chromatography-mass spectrometry (GC-MS). Result showed that 66.27% of each 100 g processed P. biglobosa seed used could be considered waste, with 23.19% in seed coat and 29.47% in effluent(s). The seed coat has moisture absorption potentials and fibrous in nature, as confirmed by proximate fibre analysis -15.03±0.13% compared to 9.07±0.10% in dried condiment. Both condiment and seed coat had considerable amount of sustenance minerals. Effluents from the boiling process had a characteristic starchy effect on textile. Concentrated effluent from the first stage of boiling had a chocolate-like aroma, sticky texture and dark-brown colour compared to the effluent from the second boiling stage. The FTIR analysis indicated the presence of alcohols, alkenes, aromatic rings, carboxylic acids, and amines in the effluent samples. GCMS characterization reported presence of specific fatty acids of known health benefits. When premised on the waste to wealth initiative, the quantified and characterized by-products of P. biglobosa seed processing as reported in this study, have potential applications across various industrial process including food, cosmetic, pharmaceutical, agriculture among others.